Which ingroup, when? Effects of gender, partisanship, veteran status, and evaluator identities on candidate evaluations. Issue 2 (15th March 2019) - Hardy, Molly M.; Coker, Calvin R.; Funk, Michelle E.; Warner, Benjamin R.
Abstract : Military service is acknowledged as one of many elements voters use to evaluate candidates, but it has primarily been studied as a univariate element of a candidate's biography. This project experimentally manipulates veteran status, gender, and partisanship as potentially interactive heuristics for evaluation of a hypothetical candidate specifically regarding military issues. We found an almost universal benefit enjoyed by veterans over civilians regardless of whether the candidate was a member of the participant's partisan ingroup or outgroup. We also found little evidence of a gender penalty, and even a benefit for women candidates who were veterans, though this benefit was restricted to evaluations from Republican women. We also found that Democratic respondents assigned a penalty to outgroup veteran men candidates. We explain these nuanced findings in the context of moderation by gender mis/alignment between participant and candidate. Implications of the study are offered.